Pretreatment with AQP4 and NKCC1 Inhibitors Concurrently Attenuated Spinal Cord Edema and Tissue Damage after Spinal Cord Injury in Rats - Yan, Xiaodong; Liu, Juanfang; Wang, Xiji; Li, Wenhao; Chen, Jingyuan; Sun, Honghui (Frontiers in Physiology, 2018)
Spinal cord injury (SCI) affects more than 2.5 million people worldwide. Spinal cord edema plays critical roles in the pathological progression of spinal cord injury. This study aimed to delineate the roles of aquaporin 4 (AQP4) and Na+-K+-Cl- cotransporter 1 (NKCC1) in acute phase edema and tissue destruction after SCI and to explore whether inhibiting both AQP4 and NKCC1 could improve SCI-induced spinal edema and damage. Rat SCI model was established by modified Allen's method. Spinal cord water content, cerebrospinal fluid lactose dehydrogenase (LDH) activity, AQP4 and NKCC1 expression, and spinal cord pathology from 30 min to 7 days after SCI were monitored. Additionally, aforementioned parameters in rats treated with AQP4 and / or NKCC1 inhibitors were assessed 2 days after SCI. Spinal cord water content was significantly increased 1 h after SCI while AQP4 and NKCC1 expression and spinal fluid LDH activity elevated 6 h after SCI. Spinal cord edema and spinal cord destruction peaked around 24 h after SCI and maintained at high levels thereafter. Treating rats with AQP4 inhibitor TGN-020 and NKCC1 antagonist bumetanide significantly reduced spinal cord edema, tissue destruction, and AQP4 and NKCC1 expression after SCI in an additive manner. These results demonstrated the benefits of simultaneously inhibiting both AQP4 and NKCC1 after SCI.